A technology foresight on electric motorcycle adoption in the Philippines through scenario building - Santos, Alvin C. (University of the Philippines Diliman, 2015)
This study entitled "A Technology Foresight on Electric Motorcycle Adoption in the Philippines" aims to determine the plausible scenarios for adoption of electric vehicles (EVs), particularly electric motorcycles, in the Philippines by 2020.